14.5k views
2 votes
THIS IS MY FIFTH TIME :(

Given the following information:
f(g) = 3t^2 – 5t +6
f(p) = 7t^2-8t^2-9
Determine f (g) + f(p) in standard form.

User Repo
by
6.0k points

1 Answer

5 votes

Answer:


f(p) + g(p) = 2t^(2)  - 5t -3 is in standard form.

Explanation:

Here. the given expressions are:


f(g)  = 3t^(2)  - 5t + 6

and
f(p) = 7t^(2)  - 8t^(2)  -9

Also, standard form of the Quadratic Equation is
ax^(2)   + bx+c

Now, computing f(g) + f(p)


= (3t^(2)  - 5t + 6 )  + (7t^(2)  - 8t^(2)  -9)\\= 3t^(2)  - 5t + 6   - t^(2)  -9) =  (3t^(2) - t^(2) )- 5t +( 6     -9) \\= 2t^(2)  - 5t -3

Or,
f(p) + g(p) = 2t^(2)  - 5t -3

User BluePsyduck
by
5.6k points